Social mobility and perinatal depression in Black women - Hawkins, Melissa; Mallapareddi, Arun; Misra, Dawn (Frontiers in Health Services, 2023)
Background Higher socioeconomic position is associated with better birth outcomes and maternal mental health, although this relationship is less consistent for Black women. The literature is limited on the impact of social mobility across the life course on mental health of pregnant women. This study examines the impact of perceived financial status across the life-course on depressive symptoms during pregnancy among Black women. Methods Data were from the Life-course Influences of Fetal Environments (LIFE) retrospective cohort study among pregnant Black women in metropolitan Detroit, Michigan. Depressive symptoms in the two weeks prior to birth were assessed using the Center for Epidemiologic Studies Depression (CES-D) scale. Social mobility was determined at three intervals over the life course using self-report of financial status during childhood, adolescence, and current age in pregnancy. Results 1,410 pregnant women participated, ranging in age from 18 to 45 years old. CES-D scores ranged from 0 to 53 (mean = 15.3) and 26% of the sample reported high depressive symptoms. In each age interval, higher financial status was associated with significant protective effect on depressive symptoms, and the magnitude of the effect increased across the life course. Trajectory analysis demonstrated that both the upward (4.51; 95% CI, 2.43–6.6) and downward (4.04; 95% CI, 2.62–5.46 and 3.09; 95% CI, 1.57–4.62) life-course social mobility groups had increased mean CES-D scores compared to the static social mobility group. Conclusion This study describes the importance of previous childhood and current financial status effects on mental health in Black pregnant women.